MODERNIZATION OF FINANCING MECHANISMS PENSION FUND IN TERMS OF COMPLIANCE WITH MODERN REQUIREMENTS OF SOCIAL POLICY - Zainalov Zh.R.; Nurmukhamedov A.M; Sharipov K.K. (Scholar Express Journals, 2023)
The article describes the transformations that have developed as a result of a long-term phased modernization of pension provision in the context of modern requirements of the social policy of the Republic of Uzbekistan in accordance with the principle of social justice. It is noted that the modernization of pension provision and the improvement of the forms and methods of mobilizing the necessary financial resources for this, involve an analysis of the economic essence of certain types of pension payments on the basis of participation in the period of working capacity or nonparticipation of a pensioner in labor activity. In addition, the article provides specific proposals to establish the level of the pension contribution of economic entities and the need to mobilize the amount of funds that can fully cover the costs associated with pension payments
Keywords: Social benefits; surcharge; source; mobilization